Agama dan Pernikahan Pasangan Beda Agama di Sendangmulyo Semarang - Irma Putri Fatimah; Amirudin Amirudin; Af'idatul Lathifah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Marriage is the dream of every couple, where marriage is one of the highest forms of commitment in every individual relationship that makes love. In practice marriage is the dream of every couple to continue to be together to build a household. However, the couple's desire now becomes complicated when the marriage is difficult because of different religious beliefs. The difficulty of the legality of interfaith marriages in Indonesia becomes a polemic of interfaith couples in carrying out their marriage legally in the state or religion or even opposition faced with the family. Given this interfaith marriage today is still intensively carried out even though in practice it is difficult to implement and many problems will arise in the future. Indonesia is indeed known as a multicultural nation where differences in culture and religion are inevitable, one of which is the phenomenon of interfaith marriages now that Indonesia has five legitimate religions and streams of belief that are still developing in modern society. The state agency appointed to legalize the holy marriage is still a long-standing polemic for some couples who want to formalize their marriage. However, because they want to keep each of their beliefs, the state fully regulates marriages that require couples to marry with the same beliefs and religions, whereas in practice citizens are free to make their own choices and have the right to be happy in determining their life choices, including in terms of marriage and determining their life partners each